2014
DOI: 10.3389/fmars.2014.00038
|View full text |Cite
|
Sign up to set email alerts
|

Marine metagenomics, a valuable tool for enzymes and bioactive compounds discovery

Abstract: The enormous potential in diversity of the marine life is still not fully exploited due to the difficulty in culturing many of the microorganisms under laboratory conditions. In this mini-review we underlined the importance of using an omics technique, such as metagenomics, to access the uncultured majority of microbial communities. We report examples of several hydrolytic enzymes and natural products isolated by functional sequenced-based and function-screening strategies assisted by new high-throughput DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Metagenomics studies from extreme environments led to the discovery of biocatalysts, secondary metabolites and bioactive compounds (Wong 2010; Barone et al 2014). For example sulphur-cycling genes from sulphidic deep sea hydrothermal vent communities (Cao et al 2014), H 2 oxidation genes from H 2 -rich serpentinite hydrothermal vent communities (Brazelton et al 2011), lipid oxidation genes in DSHV communities (He et al 2013) and genes for ammonia- oxidation (amoA) in the Guaymas Basin (Baker et al 2012) were identified by community metagenome analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomics studies from extreme environments led to the discovery of biocatalysts, secondary metabolites and bioactive compounds (Wong 2010; Barone et al 2014). For example sulphur-cycling genes from sulphidic deep sea hydrothermal vent communities (Cao et al 2014), H 2 oxidation genes from H 2 -rich serpentinite hydrothermal vent communities (Brazelton et al 2011), lipid oxidation genes in DSHV communities (He et al 2013) and genes for ammonia- oxidation (amoA) in the Guaymas Basin (Baker et al 2012) were identified by community metagenome analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Compound dereplication is one of the big hurdles in the discovery of MNPs. To achieve a simpler, faster, and more effective compound dereplication, the collected data in these databases include computational data from bioinformatics, compound curation and compilation, and experimental data from UV spectroscopy, mass spectroscopy, and nuclear magnetic resonance (NMR) . These databases deliver crucial information to the scientific community to discover new MNPs.…”
Section: Available Databases Of Mnpsmentioning
confidence: 99%
“…For example, inferences concerning the metabolic pathways for nitrogen and carbon cycling, respiration mechanisms and the degradation of particular toxic compounds can be based on the relative abundance or even the presence and absence of the relevant genes (Barone et al 2014;Narihiro et al 2014). With the constantly improved methods for sequence generation and bioinformatic analysis, near complete genome assembly is slowly becoming a standard method (Hug et al 2016).…”
Section: Genomes From Metagenomesmentioning
confidence: 99%